AB1037 Effectiveness of Conventional Dmard Therapy in Patients with Rheumatoid Arthritis and Succeeding Cost-Savings for A Health System by Diminishing Use of Biological Therapy. (15th July 2016) - Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Palacio, N.; Castro, C.; et al.
Abstract : Background: Biological therapy is useful to prevent clinical and radiological progression in patients with rheumatoid arthritis (RA) but is associated with high costs and has impacted budget in Colombian health system. Consequently, it is important to develop strategies to achieve positive outcomes in RA patients and at the same time to obtain cost-savings for health system. Objectives: We describe effectiveness of conventional DMARD therapy in RA patients with moderate-severe disease activity, usefulness of Treat to Target (T2T) strategy with a multidisciplinary care team (MCT) model and subsequently cost-savings obtained. Methods: We conducted a real-world, retrospective, cross-sectional study. We included patients who had moderate-severe disease activity; these patients were potential candidates for biologic therapy because were using conventional treatment; they were followed-up and treated according to T2T and MCT model. Clinical follow-up was designed by the authors according to DAS28 as follows: every 3–5 weeks (DAS28 >5.1), every 7–9 weeks (DAS28 ≥3.1 and ≤5.1), and every 11–13 weeks (DAS28 <3.1); therapy had to be adjusted with DAS28 >3.2 unless patient's conditions don't permit it. The aim of the study was to evaluate patients who were in moderate-severe disease activity and reached low disease activity or remission impacting on health costs. Descriptive epidemiology was done, the medians were analyzed using t-Student by performing a normality test for DAS28 distribution; the disease activity was analyzed using Pearson's statistics. Results: 526 patients were included, mean age 63.5±11.8, 424 (80%) female and 102 (20%) male. These patients had a DAS28 on average 4.5±1 at beginning and after 24 months 410 patients (78%) got remission/low disease activity status with a mean DAS28 2.57±1. The costs of biological therapy in Colombia finishing 2015 on average were $7, 725 US dollars/year/patient, and taking into account that 410 patients in moderate-severe disease activity who were candidates to biologic treatment and reached at least low disease activity, the amount in costs-savings projected for health system by preventing early use of biologics was approximately $3, 167, 551million dollars/year, ranging between the cheapest biological and the most expensive ($4, 878 and $12, 774 US dollars/year respectively). Conclusions: This study showed that it is possible to decrease disease activity and obtain a significant cost-reduction in treatment of RA by using conventional DMARDs in a model with therapeutic goals like T2T and optimizing a multidisciplinary approach. Disclosure of Interest: None declared